Evaluación de dos protocolos de IATF sobre la Tasa de Preñez y los niveles de LH en vaconas mestizas del CIPCA (Centro de Investigación, Posgrado y Conservación Amazónica) cantón Carlos Julio Arosemena Tola, Provincia de Napo - Bautista Solis, Alex Rolando (2015)
The research aim was the two - protocols evaluation on pregnancy rate and LH levels in crossbreed heifers of CIPCA. There were selected 40 crossbreed heifers and they were chosen randomly for treatments. The Crestar® treatment consisted of placing ear implant Norgestomet on day 0, the implant was removed on day 7 th and it applied 150 ug of PG2α (BioprostD biotay) + 2 mg ECP (Cipionato of Estradiol-Pfizer) + 400 UI eCG (Folligón) and the IATF was performed 52 hours after the implant it also applied on the insemination day 0,2 mg GnRH (Fertagyl®) and it took out blood sample to analyze LH levels. The DIB treatment consisted of the application of progesterone intravaginal device on the day 0, seven days later the DIB was removed and also it applied 150 ug de PG2α (BioprostD biotay) and the IATF was performed 52 hours after the implant it also applied on the insemination day 0,2 mg GnRH (Fertagyl®) and it took out blood sample to analyze LH levels. The pregnancy diagnosis was determined by transrectal ultrasonography 42 days after IATF....